Potensi aktivitas antioksidan ekstrak spons laut Stylissa carteri: Potential antioxidant activity of sea sponge Stylissa carteri extract - Adewal, Murad Alvian K; Abdullah, Asadatun; Zamani, Neviaty Putri; Arafat, Dondy; Ayu, Inna Puspa; Subhan, Beginer (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2025)
The sea sponge Stylissa carteri plays an important role because it is one of the constituent biota of coastal and marine ecosystems, especially in coral reef ecosystems. The increasing utilization of bioactive compounds in sea sponges is feared to significantly reduce the population of sea sponges. The prevention effort involves cultivating sea sponges for sustainable utilization. This study aims to determine the antioxidant activity of transplanted Stylissa carteri sponges and those that live naturally in nature. This study was conducted in Pramuka Island using the sponge explant combination method. The three types of transplants were number one (SO), number two (S. carteri and Aaptos suberitoides), and number three (S. carteri, A. suberitoides, and Acropora hard coral). Antioxidant activity was tested with three repetitions on three transplanted and naturally occurring S. carteri sponges (SA) using the DPPH (1,1-Diphenyl-2-Picrylhydrazyl) method. The results indicated that the four sample sources contained strong antioxidant activity, namely SO had an IC50 value of 86.22±23.6 μg/mL, SAP 86.58±30.7 μg/mL, SAC 86.10±23.4 μg/mL, and natural living SA 54.27±16.9 μg/mL. The transplanted S. carteri sea sponge has strong antioxidant activity and can be an alternative solution in terms of raw material availability for the development of potential pharmaceutical products.